The role of stress management and interpersonal communication in preventing violence against family physicians - Ardic, Cuneyt; Ozturk, Guzin Zeren (International Journal of Research in Medical Sciences, 2018)
Background: Family physicians are the first line of contact with patients seeking primary care services. Therefore, they are vulnerable to violence from patients and family members. Therefore, aim of this study was to determine of stress management and interpersonal communication of the family physicians and examine the role of stress management and interpersonal communication to prevent violence. Methods: 736 family physicians were participated from 37 different provinces of Turkey. The scores of stress management and interpersonal communication were compared according to violence situations. Results: A 20.65% (n = 152) of the physicians participating in the study were subjected to physical violence; their interpersonal communication scores were significantly lower than those of physicians who had not been subjected to physical violence (p = 0.022). Among the participants, 90.77% (n = 668) were subjected to verbal violence; their interpersonal communication scores were significantly lower than those of participants who had not been subjected to verbal violence (p = 0.012). Although the interpersonal communication scores were low and statistically related at the participants who had been subjected to violence. Conclusions: This study revealed that the interpersonal communication and stress management scores were low at the participants who had been subjected to violence; only interpersonal communication was statically related. Therefore, stress management and interpersonal communication is very important to protect from violence, we suggested that this should be part of the curriculum of medical schools and postgraduate education.